Additional Imaging is of Limited Value in Traumatic Hip Fractures With a History of Distant Malignancy and No Suspicious Lesion on Plain Radiographs. Issue 11 (November 2022) - Sharrock, Martin; Mati, Wael; Peng Koh, Shang; Abdullah, Mustafa; Charalambous, Charalambos P.
Abstract : Objective: To determine the value of obtaining additional preoperative imaging in patients with a traumatic hip fracture and a history of malignancy in whom plain radiographs show no lesion suspicious for metastases. Design: Retrospective review. Setting: Teaching NHS Trust in the United Kingdom, over an 8-year period treating 4421 hip fractures. Patients/Participants: Three hundred sixty-seven patients with hip fracture and a history of malignancy at a site distant to the hip. Three hundred thirty patients had a history of trauma and no lesion on the plain radiograph suspicious for metastases. Main Outcomes Measurements: Whether obtaining additional imaging preoperatively (MRI, CT, and bone scan) identified metastases or affected management. Results: 32/330 patients had further preoperative imaging, none of which demonstrated a pathological fracture secondary to malignancy. On follow-up, 3/330 (0.9%) cases were found to have occult metastasis at the hip fracture site. All 3 had only plain radiographs before surgery. In 2, this was identified on histological examination of intraoperative samples, and in 1, radiologically as a metastatic metaphyseal lesion 18 months after a hemiarthroplasty. Only in the latter case, preoperative identification of hip metastasis could have altered surgical management. Patients undergoing further preoperative imaging waited significantly longer for surgery (35 ± 26 vs. 51 ± 26 hours, P = 0.0011). Conclusions: In the absence of a suspicious metastatic lesion on initial plain radiographs, further preoperative imaging is unlikely to identify a lesion that will affect management and confers significant delays to surgery. Sending intraoperative histological samples may help guide postoperative oncological management, but further work is needed to prove its utility. Level of Evidence: Diagnostic Level IV. See Instructions for Authors for a complete description of levels of evidence.